Incorporating Eastern and Western Learning Perspectives into Western Learning Environment - Chang, Bo (Journal of Interdisciplinary Studies in Education, 2021)
This paper focuses on incorporating Eastern and Western learning perspectives into an American learning environment. The design-based research approach is employed. The following principles influenced by the Eastern and Western perspectives of learning were implemented in course design: providing pre-sequenced materials with high structure and flexible options, valuing group collaboration and individual autonomy, and promoting diverse ideas and critical thinking. Responses from 38 participants show that students from the Western learning environment also favor the pre-sequenced course materials with high structure. Even though they prefer independent and individual work, in an online environment a certain degree of collaborative work is necessary to create interactive dynamics and a sense of presence. Critical thinking in an online environment is not always adequately executed, which does not support the Western learning perspective of favoring critical thinking.